Monitoring of nitrate contamination in groundwater: case study of the campus of UNESP, Rio Claro/SP - Teramoto, Elias Hideo; Costa, Pedro Paulo Bazilio da; Gonçalves, Roger Dias; Engelbrecht, Bruno Zanon; Chang, Hung Kiang (Ciência e Natura, 2019)
This study presents the results of the monitoring of nitrate concentrations in shallow groundwater at the UNESP Campus of Rio Claro/SP assumed to be sourced by septic tank leakage, which were discontinued in October 2014. The distribution of nitrate concentrations provides support to a conceptual model of contamination by multiple sources, since the concentration gradients are not observed along the flowpaths. The results of the monitoring indicate that in some monitored wells, the nitrate concentrations remain stable, while in other wells minor to strong fall trends were observed. These results provide support to the presence of other active sources, such as sewage leakage in the external and internal area of the campus. This scenario perfect fit with the maintenance of recorded high nitrate concentrations over the time. Despite the nitrate concentrations are below potability limit, additional investigations will be conducted to identify sources of contamination to ensure water quality in the future.